Association of the cystatin C/creatinine ratio with the renally cleared hormones parathyroid hormone (PTH) and brain natriuretic peptide (BNP) in primary care patients: a cross-sectional study. (3rd July 2016) - Risch, Martin; Risch, Lorenz; Purde, Mette-Triin; Renz, Harald; Ambühl, Patrice; Szucs, Thomas; Tomonaga, Yuki
Abstract: The ratio of cystatin C to creatinine (cysC/crea) is regarded as a marker of glomerular filtration quality and predicts mortality. It has been hypothesized that increased mortality may be mediated by the retention of biologically active substances due to shrinking glomerular pores. The present study investigated whether cysC/crea is independently associated with the levels of two renally cleared hormones, which have been linked to increased mortality. We conducted a multicenter, cross-sectional study with a random selection of general practitioners (GPs) from all GP offices in seven Swiss cantons. Markers of glomerular filtration quality were investigated together with estimated glomerular filtration rate (eGFR), albuminuria and urinary neutrophil gelatinase associated lipocalin (uNGAL) as well as two renally cleared low-molecular-weight protein hormones (i.e. BNP and PTH), Morbidity was assessed with the Charlson Comorbidity Index (CCI). A total of 1000 patients (433 males; mean age 57 ± 17 years) were included. There was a significant univariate association of BNP ( r = 0.36, p < 0.001) and PTH ( r = 0.18, p < 0.001) with cysC/crea. An adjusted model that accounted for kidney function (eGFR), altered glomerular structure (albuminuria), renal stress (uNGAL), and CCI showed that BNP and PTH were independently associated with cysC/crea as well as with the ratio of cystatin C-based to creatinine-based eGFR. In conclusion, in primary care patients, BNP and PTH are independently associated both with markers of glomerular filtration quality and eGFR regardless of structural kidney damage or renal stress. These findings offer an explanation, how altered glomerular filtration quality could contribute to increased mortality.